2007
DOI: 10.1111/j.1365-2958.2007.05678.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth phenotypes of Pseudomonas aeruginosa lasR mutants adapted to the airways of cystic fibrosis patients

Abstract: SummaryThe opportunistic pathogen Pseudomonas aeruginosa undergoes genetic change during chronic airway infection of cystic fibrosis (CF) patients. One common change is a mutation inactivating lasR, which encodes a transcriptional regulator that responds to a homoserine lactone signal to activate expression of acute virulence factors. Colonies of lasR mutants visibly accumulated the iridescent intercellular signal 4-hydroxy-2-heptylquinoline. Using this colony phenotype, we identified P. aeruginosa lasR mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
374
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 326 publications
(393 citation statements)
references
References 116 publications
(200 reference statements)
18
374
1
Order By: Relevance
“…Recent reports revealed that a considerable proportion of P. aeruginosa isolates from CF patients possess mutations in the lasR gene (12,19). Being contradictory to the current view that the lasR-mediated QS system is essential for P. aeruginosa virulence, these findings suggest that (i) QS in the CF airway may not be required for bacterial survival, especially at the chronic stage, and (ii) QS regulation may occur differently under conditions with reduced oxygen tension.…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…Recent reports revealed that a considerable proportion of P. aeruginosa isolates from CF patients possess mutations in the lasR gene (12,19). Being contradictory to the current view that the lasR-mediated QS system is essential for P. aeruginosa virulence, these findings suggest that (i) QS in the CF airway may not be required for bacterial survival, especially at the chronic stage, and (ii) QS regulation may occur differently under conditions with reduced oxygen tension.…”
contrasting
confidence: 55%
“…However, recent genetic studies using diverse P. aeruginosa clinical isolates reported that adaptive mutations in the lasR gene occur spontaneously in the course of chronic airway infection in CF (9,12,19,42). Phenotype on April 7, 2019 by guest http://iai.asm.org/ changes conferred on P. aeruginosa by these mutations include (i) facilitated growth on amino acids present in relatively large quantities in CF airways (1,12), (ii) an efficient shift to an anaerobic mode of growth using nitrate over oxygen (20), and (iii) elevated antibiotic resistance (12,20). Therefore, frequent identification of lasR mutants suggests that P. aeruginosa may acquire the mutation to increase its survival fitness in a harsh host environment at the expense of its ability to regulate QS-mediated virulence properties.…”
Section: Discussionmentioning
confidence: 99%
“…Following colonization of the CF lung, P. aeruginosa undergoes a number of repeatable genetic changes, such as mutations to lasR and mucA (D'Argenio et al, 2007;Mathee et al, 2008;Rau et al, 2010;Rowen & Deretic, 2000), that have not been reported in other types of infection. Epistatic interactions between quinolone-resistance mutations and these presumably CF-adaptive mutations may therefore underlie differences in patterns of clinical resistance mutations.…”
Section: Hypothesis 3: Epistasismentioning
confidence: 99%
“…Whole-genome sequencing of early-and late-stage isolates of P. aeruginosa from a CF patient showed that lasR was inactivated in the late-stage infection isolate (Smith et al, 2006). In a follow-up study, comparing isolates from the same patient over an 8 year period, lasR mutants could be detected in isolates obtained after approximately 2 years of infection (D'Argenio et al, 2007). However, wild-type strains could also be detected until approximately 5 years post-infection, after which time all of the isolates tested carried a single lasR mutation, suggesting that loss of LasR occurs over time (D'Argenio et al, 2007).…”
Section: Identification Of Qs Signals and Regulated Products From CLImentioning
confidence: 88%
“…In a follow-up study, comparing isolates from the same patient over an 8 year period, lasR mutants could be detected in isolates obtained after approximately 2 years of infection (D'Argenio et al, 2007). However, wild-type strains could also be detected until approximately 5 years post-infection, after which time all of the isolates tested carried a single lasR mutation, suggesting that loss of LasR occurs over time (D'Argenio et al, 2007). The clonal lineage of P. aeruginosa strains from Australia, whilst retaining QS genes, often do not produce the QS signals, at least in vitro (Tingpej et al, 2007).…”
Section: Identification Of Qs Signals and Regulated Products From CLImentioning
confidence: 99%